The naval main engines parameters variation, due different external factors. Issue 1 (September 2020) - Serbanescu, I; Stan, L
Abstract: In this paper, we carried out a real and simulated study, regarding the naval main engines parameters variation on different external factors. The ships, was in normal operation mode, at various around the globe points, so different environmental external conditions. It is worth mentioning that such studies help us to better understand the operating processes of naval propulsion engines, under different environmental conditions. We can also draw conclusions on how to improve the operating mode of these types of engines. Such tests cannot be carried out in the factory condition, only in operation mode with the ship under way. In particular, the studied parameters of the engines were: average effective pressure, average effective power and maximum combustion pressure. As external factors that have been taken into account I mention: ambient temperature, sea water temperature, supercharger pressure. The study was conducted on two known types of naval propulsion engines. The first most common is the MAN B&W 6S35MC-MK7, in this case being a propulsion engine for a tanker. The second type of naval propulsion engine is in a reefer container ship, the engine being a Sultzer 9RND-90M. The experimental or simulated determinations carried out on board the ships, were made using the existing specific reading devices. Using data obtained by direct reading or performed countless thermal calculations for each engine. There followed the interpretation of the final data obtained, many being presented graphically. The final conclusions were followed, which led to a more efficient operation by regulating certain operating parameters, such as the temperature of the supercharger air under different atmospheric weather conditions.